Gene and Protein Expression in Subjects With a Nystagmus-Associated AHR Mutation - Borovok, Natalia; Weiss, Celeste; Sharkia, Rajech; Reichenstein, Michal; Wissinger, Bernd; Azem, Abdussalam; Mahajnah, Muhammad (Frontiers in Genetics, 2020)
Recently, a consanguineous family was identified in Israel with three children affected by Infantile Nystagmus and foveal hypoplasia, following an autosomal recessive mode of inheritance. A homozygous stop mutation c.1861C>T;p.Q621* in the AHR (AHR; MIM 600253) gene was identified that co-segregated with the disease in the larger family. AHR is the first gene to be identified causing an autosomal recessive Infantile Nystagmus-related disease in humans. The goal of this study is to delineate the molecular basis of a newly discovered human genetic disorder associated with the rare AHR gene mutation. The gene and protein expression levels of AHR and selected AHR targets from leucocytes cultures of healthy subjects and the patients were analyzed. We observed significant alterations between mRNA and protein expression of CYP1A1, CYP1B1, and TiPARP under rest and AHR-induced by benzo-(a)-anthracene conditions. The CYP1A1 enzymatic activity in induced leucocytes also shows strong differences between the patients and healthy volunteers. Intriguingly, the heterozygous subjects demonstrate similarities with homozygous patients in CYP1A1 and TiPARP gene and protein expression. The CYP1B1 exhibits diverse between inducibility and expression in hetero- and homozygous subjects. Similarity and differences in gene and protein expression between heterozygotes and homozygous patients can give us a hint as to which metabolic pathway/s might be involved in the Nystagmus etiology. Thus, we have a unique opportunity to study the biochemical basis of this rare human mutation as well as the involvement of AHR in other physiological processes. This family considers as unique human model for AHR deficiency.